PENYULUHAN DAN PELATIHAN PEMANFAATAN BUNGA TELANG MENJADI PRODUK KAYA ANTIOKSIDAN UNTUK MENINGKATKAN KESEHATAN DI DESA ULAK KERBAU BARU TANJUNG RAJA - Dina Permata Wijaya; Herlina Herlina; Dian Wahyuni; Puspa Ayu Pitayati (Jurnal Abdi Insani, 2023)
Butterfly pea flower is a flower plant that can grow in the yard or can live ini the forest. Butterfly pea flowers have secondary metabolites that can be used for health, including flavonoids, phenols, anthocyanins, alkaloids, steroid triterpenoids, and flavonol glycosides. Butterfly pea flower ia a plant that has been widely consumed by the public as a functional food and beverage ingredient which has the benefit of being an antioxidant so it can improve helath. The purpose of this activity is to increase public understanding regarding the importance of improving post endemic COVID-19 by consuming antioxidant-rich foods and drinks and improving the economy in Ulak Kerbau Baru Tanjung Raja Village. Methods of community service activities in the form of counselling and providing education, product manufacturing practices, and assistance. Products made in this community service activity are jelly candy and carbonated drinks made from butterfly pea flowers. Community service activities wera carrued out in approximately 2 month for the people of Ulak Kerbau Baru Tanjung Raja Village. Prior to the practice of making jelly candy and carbonated drinks from butterfly pea flowers, the community was given material related to the use of butterfly pea flowers to improve helath because they contain lots of antioxidants. Many people in Ulak Kerbau Baru Village dont know that butterfly pea flowers can improve helath and can be used as food and drink products that taste delicious. Making simple jelly and carbonated drinks so that people can make them ath homen can also be used as products for businesses. Based on the results of this community service activity, there is an increase in public knowledge of the importance of improving health and the utilization of butterfly pea flowers into food and beverage products with a delicious taste and the community gaining skills to made jelly candy and carbonated drinks product form butterfly pea flowers.